Physiological Impacts of Cauliflower in Hyperthyroid Rabbits - Al-Jowari, Suha Abdul-Khaliq (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
This study aimed to investigate the effect of cauliflower extract as a remedy for hyperthyroid in rabbits. Twenty rabbits with mean weight 1700 ±95 g and age of 6-7 months were chosen. The animals were randomly divided into four groups (five in each group). The first group (GI) was the control and received normal diet and given tap water. The second and third groups (GII & GIII) were received 30 μg/Kg BW sodium L-Thyroxin injected subcutaneously to induce hyperthyroidism for three weeks. After that, these groups (GII & GIII) were administrated 20 & 30 mg/kg of body weight cauliflower extract for four weeks. Blood samples were collected from hyperthyroid and treated groups after two and four weeks. Serum was centrifuged at 3000 rpm for 15 minutes. The collected serum was used in the assessment of the levels of thyroxine (T4), triiodothyronine (T3) and thyroid stimulating hormones (TSH) by analytical kits which determined on ELISA method. Further, a molecular study was performed to estimate TSHR gene expression. The results of the present work showed that there was a significant (p<0.05) decrease in T3 and T4 hormone levels means in rabbits treated with cauliflower extract as compared with hyperthyroid. It concluded from the present study that the natural products such as phenolic compounds, carotenoids, flavonoid, and ascorbic acid from cauliflower might be used as a remedy to recover from hyperthyroid states in order to reduce the intake of chemical drugs.